Cloud Technology as a New Approach for Effective Education - Aminov I.B.; Sharapova N.A. (International Journal on Human-Computing Studies, 2024)
One of the tasks of the education system in modern society is to provide each person with free and open access to education throughout his life, taking into account his interests, abilities and needs. The article considers the possibilities of using cloud technologies in education, and also presents the main examples of modern services built on the basis of cloud computing technology for education.